A multi-component patient-handling intervention improves attitudes and behaviors for safe patient handling and reduces aggression experienced by nursing staff: A controlled before-after study. (April 2017) - Risør, Bettina Wulff; Casper, Sven Dalgas; Andersen, Lars Louis; Sørensen, Jan
Abstract: This study evaluated an intervention for patient-handling equipment aimed to improve nursing staffs' use of patient handling equipment and improve their general health, reduce musculoskeletal problems, aggressive episodes, days of absence and work-related accidents. As a controlled before-after study, questionnaire data were collected at baseline and 12-month follow-up among nursing staff at intervention and control wards at two hospitals. At 12-month follow-up, the intervention group had more positive attitudes towards patient-handling equipment and increased use of specific patient-handling equipment. In addition, a lower proportion of nursing staff in the intervention group had experienced physically aggressive episodes. No significant change was observed in general health status, musculoskeletal problems, days of absence or work-related accidents. The intervention resulted in more positive attitudes and behaviours for safe patient-handling and less physically aggressive episodes. However, this did not translate into improved health of the staff during the 12-month study period. Highlights: Patient-handling by nurses increases back-injuries and aggressive incidences. We evaluated an intervention for patient-handling equipment. Intervention and control wards provided baseline and 12-month follow-up data. Intervention improved nursing staff. No changes were found in general health, days of absence or work-related accidents.